Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/10803548.2014.11077068
|View full text |Cite
|
Sign up to set email alerts
|

Noise Pollution in Metalwork and Woodwork Industries in the Kingdom of Saudi Arabia

Abstract: This study was conducted in metalwork and woodwork industries in Jeddah Industrialindustrial noise metalwork woodwork noise control Saudi Arabia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
13
0
2
Order By: Relevance
“…In the present study, we included area measurements to investigate the compliance between these measurements and corresponding personal measurements. Area measurements using sound level meter have been widely used to indicate workers’ noise exposure in regions of limited economic resources including African and Asian countries ( Pandya and Dharmadhikari, 2002 ; Warrington and McLoughin, 2005 ; Ologe et al ., 2006 ; Singh et al ., 2013 ; Noweir et al ., 2014 ). Some reasons to this could be that the method is relatively inexpensive by using only one instrument, it is easy to conduct, and it takes less time than personal measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we included area measurements to investigate the compliance between these measurements and corresponding personal measurements. Area measurements using sound level meter have been widely used to indicate workers’ noise exposure in regions of limited economic resources including African and Asian countries ( Pandya and Dharmadhikari, 2002 ; Warrington and McLoughin, 2005 ; Ologe et al ., 2006 ; Singh et al ., 2013 ; Noweir et al ., 2014 ). Some reasons to this could be that the method is relatively inexpensive by using only one instrument, it is easy to conduct, and it takes less time than personal measurements.…”
Section: Discussionmentioning
confidence: 99%
“…This region is estimated to have an increasing occurrence of occupational-related noise-induced hearing loss due to rapid ongoing industrialization ( Concha-Barrientos et al ., 2004 ; Nelson et al ., 2005 ). Research has shown that iron and steel factories in industrialized countries are among the workplaces with high noise levels ( Lie et al ., 2016 ), but only a few studies have been conducted in developing countries on noise exposure in these same industries ( Kamal et al ., 1989 ; Pandya and Dharmadhikari, 2002 ; Ologe et al ., 2006 ; Singh et al ., 2013 ; Noweir et al ., 2014 ). To our knowledge, no such studies have been undertaken in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Noise pollution was pervasive even in U.S. protected areas [39]. Workplace health hazard of noise pollution were documented in factories [40], metalwork and woodwork industries [41], commercial banks [42], traffic [43][44], emergency wards [45], and small-scale industries [46].…”
Section: Introductionmentioning
confidence: 99%
“…They influence heat generation due to friction between tool and workpiece in the metalworking processes . Moreover, the processes also produce lots of dust, pollutants and noise . To overcome this problem, metalworking fluids are commonly used .…”
Section: Introductionmentioning
confidence: 99%